A Yolk–Shell‐Structured FePO4 Cathode for High‐Rate and Long‐Cycling Sodium‐Ion Batteries - Zhang, Zhuangzhuang; Du, Yichen; Wang, Qin‐Chao; Xu, Jingyi; Zhou, Yong‐Ning; Bao, Jianchun; Shen, Jian; Zhou, Xiaosi (Angewandte Chemie International Edition, 2020)
Amorphous iron phosphate (FePO4) has attracted enormous attention as a promising cathode material for sodium‐ion batteries (SIBs) because of its high theoretical specific capacity and superior electrochemical reversibility. Nevertheless, the low rate performance and rapid capacity decline seriously hamper its implementation in SIBs. Herein, we demonstrate a sagacious multi‐step templating approach to skillfully craft amorphous FePO4 yolk–shell nanospheres with mesoporous nanoyolks supported inside the robust porous outer nanoshells. Their unique architecture and large surface area enable these amorphous FePO4 yolk–shell nanospheres to manifest remarkable sodium storage properties with high reversible capacity, outstanding rate performance, and ultralong cycle life. FePO4 nanospheres consisting of mesoporous nanoyolks supported inside robust porous nanoshells are synthesized by a judicious multi‐step templating strategy using carbon nanospheres as the starting material. Their architecture and composition allow these hierarchical FePO4 yolk–shell nanospheres to manifest excellent sodium storage performance as a cathode material for sodium‐ion batteries.